Empagliflozin inhibits coronary microvascular dysfunction and reduces cardiac pericyte loss in db/db mice - Tu, Yimin; Li, Qing; Zhou, Yuanchen; Ye, Zixiang; Wu, Chao; Xie, Enmin; Li, Yike; Li, Peizhao; Wu, Yaxin; Guo, Ziyu; Yu, Changan; Zheng, Jingang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary microvascular dysfunction (CMD) is a pathophysiological feature of diabetic heart disease. However, whether sodium-glucose cotransporter 2 (SGLT2) inhibitors protect the cardiovascular system by alleviating CMD is not known. Objective We observed the protective effects of empagliflozin (EMPA) on diabetic CMD. Materials and Methods The mice were randomly divided into a db/db group and a db/db+EMPA group, and db/m mice served as controls. At 8 weeks of age, the db/db+EMPA group was given empagliflozin 10 mg/(kg·d) by gavage for 8 weeks. Body weight, fasting blood glucose and blood pressure were dynamically observed. Cardiac systolic and diastolic function and coronary flow reserve (CFR) were detected using echocardiography. The coronary microvascular structure and distribution of cardiac pericytes were observed using immunofluorescence staining. Picrosirius red staining was performed to evaluate cardiac fibrosis. Results Empagliflozin lowered the increased fasting blood glucose levels of the db/db group. The left ventricular ejection fraction, left ventricular fractional shortening, E/A ratio and E/e’ ratio were not significantly different between the three groups. CFR was decreased in the db/db group, but EMPA significantly improved CFR. In contrast to the sparse and abnormal expansion of coronary microvessels observed in the db/db group, the number of coronary microvessels was increased, and the capillary diameter was decreased in the db/db+EMPA group. The number and microvascular coverage of cardiac pericytes were reduced in the db/db mice but were improved by EMPA. The cardiac fibrosis was increased in db/db group and may alleviate by EMPA. Conclusion Empagliflozin inhibited CMD and reduced cardiac pericyte loss in diabetic mice.